An efficient hybrid technique for the solution of fractional-order partial differential equations - Jassim, H.K.; Ahmad, H.; Shamaoon, A.; Cesarano, C. (Carpathian Mathematical Publications, 2021)
In this paper, a hybrid technique called the homotopy analysis Sumudu transform method has been implemented solve fractional-order partial differential equations. This technique is the amalgamation of Sumudu transform method and the homotopy analysis method. Three examples are considered to validate and demonstrate the efficacy and accuracy of the present technique. It is also demonstrated that the results obtained from the suggested technique are in excellent agreement with the exact solution which shows that the proposed method is efficient, reliable and easy to implement for various related problems of science and engineering.